Social psychology : conflicts and continuities : an introductory textbook - Howitt, Dennis, et al.; Billlig,michael; Cramer,Duncan; Edwards,Derek; Kniveton,Bromley; Potter,Jonathan; Radley,Alan (New Delhi: Tata McGraw Hill Education Private Limited, 2010)
Emphasises the underlying ideas and intellectual debates in social psychology. It explores fundamental disagreements about what sorts of theories, what sorts of research methods, what sorts of issues, questions and answers are right for social psychology.
Keywords: Social psychology